Controle de qualidade em equipamentos de tomografia computadorizada - Cechinato, Mariana [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
The computed tomography, devised by Godfrey Hounsfield and Allan Cormack, is in its fourth decade of the clinical use and has presented to be a very useful tool in the diagnosis of several pathologies. For this reason, its use is increasing each day, due to technological progress since its creation. Due to be more and more utilized, the equipment must be in good operating conditions, because it is subject to variance and wearing, damage the quality of diagnosis. To evaluate whether the performance of the scanner remains constant along the time and the dose received by the patient is within the desired limits, periodic tests of quality control must be performed. For this subject, the regulation 453 (June 01, 1998) was created, which determines the need of the implementation of a program for quality assurance (PGQ), where, in addition to the tests of quality control, are established the necessary measurements for the proper functioning of the equipment, generating a trustworthy diagnosis, reducing the dose for the patient and the costs. In this document, are presented tests of quality control carried out in hospitals of the city of Sao Paulo carried out together with the Technical Section of Applications by Imaging Diagnostic (STADI) of the Institute of Electrotechnics and Energy of the University of São Paulo (IEE/USP)

A tomografia computadorizada, idealizada por Godfrey Hounsfield e Allan Cormack, está em sua quarta década de utilização clínica e tem se mostrado uma ferramenta muito útil no diagnóstico de diversas patologias. Por essa razão, sua utilização vem crescendo a cada dia, devido aos grandes avanços tecnológicos desde sua criação. Por ser cada vez mais utilizado, o equipamento deve estar em boas condições de funcionamento, pois está sujeito a alterações e desgaste, prejudicando a qualidade do diagnóstico. Para avaliar se o desempenho do tomógrafo se mantém constante com o tempo e a dose recebida pelo paciente esteja dentro dos limites desejados, devem ser realizados testes periódicos de controle de qualidade. Para que isto ocorra, foi criada a Portaria 453 (01 de junho de 1998), que determina a necessidade de implantação de um Programa de Garantia de Qualidade (PGQ), onde, além dos testes de controle de qualidade, ficam estabelecidas as medidas necessárias para um funcionamento adequado do equipamento, gerando um diagnóstico confiável, com redução da dose para o paciente e dos custos. Neste trabalho, são apresentados testes de controle de qualidade realizados em hospitais da cidade de São Paulo realizados juntamente com a Seção Técnica de Aplicações em Diagnósticos por Imagem (STADI) do Instituto de Eletrotécnica e Energia da Universidade de São Paulo (IEE/USP)
Keywords: Diagnóstico por imagem; Tomografia - Controle de qualidade; Fisica medica